High performance magnetic carbonaceous materials as a photo Fenton-like catalyst for organic pollutant removal. (June 2022) - Saputra, Edy; Prawiranegara, Barata Aditya; Sugesti, Heni; Fadli, Ahmad; Heltina, Desi; Utama, Panca Setia; Azis, Yelmida; Manawan, Maykel; Wang, Shaobin; Oh, Wen-Da
Abstract: Herein, three different catalysts, namely carbon nanosphere (CS), Fe3 O4 @CS, and Fe3 O4 @g-C3 N4 /CS, were synthesized by a facile one-pot hydrothermal carbonization approach. X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET) surface area analysis, UV–vis diffuse reflectance spectra (UV-DRS), and FT-IR spectra were conducted to study the chemical and physical properties of the catalysts. Thereafter, the catalysts were used for catalytic degradation of methylene blue (MB) in a visible light Fenton-like process. The catalytic activity for MB degradation shows an order of CS < Fe3 O4 @CS < Fe3 O4 @g-C3 N4 /CS. The catalytic system process using Fe3 O4 @g-C3 N4 /CS can effectively remove 99.9% of MB at 30 mg/L. Overall, the Fe3 O4 @g-C3 N4 /CS-photo Fenton-like system displays promising performance for the degradation of MB. Graphical abstract: Unlabelled Image Highlights: CS, Fe3 O4 @CS, and Fe3 O4 @g-C3 N4 /CS were synthesized by a facile one-pot hydrothermal carbonization approach (HCA). Fe3 O4 @g-C3 N4 /CS presented the highest activity in the methylene blue oxidation. Fe3 O4 @g-C3 N4 /CS showed to be a promising catalyst and simple separation. Methylene blue degradation on Fe3 O4 @g-C3 N4 /CS followed pseudo-first-order kinetics.